MicroRNA regulation of glycolytic metabolism in glioblastoma multiforme - Alfardus, Huda; McIntyre, Alan; Smith, Stuart J. (Hindawi Publishing Corporation, 2017)
Glioblastoma multiforme (GBM) is the most aggressive and common malignant brain and central nervous system tumour. A well-known hallmark of GMB, and many other tumours, is aerobic glycolysis. microRNAs (miRNAs) are a class of short non-protein coding sequences that exert post-transcriptional controls on gene expression and represent critical regulators of aerobic glycolysis in GBM. In GBM, miRNAs regulate the expression of glycolytic genes directly and via the regulation of metabolism-associated oncogenic pathways, such as the PI3K/Akt signalling pathway. The aim of this review is to establish links between miRNA expression levels, disease grade and prognosis, and the glycolytic phenotype of GBM. In this review, the involvement of 25 miRNAs in the regulation of glycolytic metabolism of GBM is discussed. Seven of these miRNAs have been shown to regulate glycolytic metabolism in other tumour types. Further eight miRNAs, which have been shown to be differentially expressed in GBM, were also reported to play a regulatory role in glycolysis in other cancer types. Such miRNAs could serve as potential glycolytic regulators in GBM but require functional validation. This review concludes with presenting a number of glycolytic regulatory miRNAs that have demonstrated their therapeutic potential either alone or as adjuvants in GBM, despite the major challenges that have to be solved before miRNA-based therapies can widely be used for the treatment of GBM patients.